Highly dispersed oleic-induced nanometric C@Na3V2(PO4)2F3 composites for efficient Na-ion batteries. (1st February 2020) - Criado, A.; Lavela, P.; Ortiz, G.; Tirado, J.L.; Pérez-Vicente, C.; Bahrou, N.; Edfouf, Z.
Abstract: C@Na3 V2 (PO4 )2 F3 samples were synthesized by an emulsion method using oleic acid as a surfactant and Vaseline oil as organic media of the micellar system. Their structural, chemical and morphological properties are determined by at the light of solid-state techniques, including X-ray diffraction, electron microscopy, and Raman and XPS spectroscopies. Electrochemical tests, performed by the galvanostatic method, show that the use of oleic acid as a surfactant improves the electrode kinetic properties and consequently the electrochemical behavior as a cathode for sodium-ion batteries. Graphical abstract: Image 1 Highlights: C@Na3 V2 (PO4 )2 F3 samples were synthesized by an emulsion method using oleic acid as a surfactant. Oleic acid favors nanometric particles homogeneously embedded into the carbon conductive phase. An equivalent ratio of citric to oleic acid provided a nanometric mosaic-like texture. Oleic-based sample retained 84% of the initial capacity after 200 cycles at 2C.